Community-Based Literacy Programs and Their Effect on Learning Motivation and Academic Performance - Aries Denta Putra (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2025)
Community-based literacy programs have emerged as an important strategy to improve educational outcomes by engaging communities in supporting learners’ literacy development beyond formal schooling. This study aims to analyze the effect of community-based literacy programs on students’ learning motivation and academic performance. The research employs a quantitative approach using survey and academic performance data collected from participants involved in community literacy initiatives. The programs typically include reading clubs, community tutoring sessions, mobile libraries, and collaborative learning spaces designed to strengthen reading habits and provide academic assistance. The findings indicate that participation in community-based literacy programs significantly contributes to increased learning motivation among students. Learners involved in such programs demonstrate greater enthusiasm for reading, improved learning discipline, and stronger engagement in classroom activities. Furthermore, improved literacy skills positively influence academic achievement, particularly in language-related subjects and overall academic performance. The study also reveals that community participation, availability of learning resources, and supportive learning environments are crucial factors determining program success. However, challenges such as limited funding, inconsistent program management, and unequal access to literacy facilities remain obstacles in maximizing program outcomes. Strengthening partnerships between schools, communities, and local governments is essential to ensure program sustainability and broader impact. The study concludes that community-based literacy programs play a vital role in enhancing students’ motivation and academic achievement by creating supportive learning ecosystems beyond school settings. Therefore, integrating community literacy initiatives into broader educational development policies is recommended to improve long-term learning outcomes and educational equity.